The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.31235/osf.io/7pkqg
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lifecourse Trajectories and Cross-generation Trends in Social Isolation: Findings from Five Successive British Birth Cohort Studies

Abstract: Despite growing concerns in the UK about social isolation, there remains a lack of evidence on the extent and time trends of social isolation from longitudinal, population-based studies. There is also little research that assesses the multiple domains of social isolation across the lifecourse and between generations in a holistic way accounting for different contexts. By applying a multi-context, multiple-domain framework of social isolation to 5 successive British birth cohorts, we provide conceptual and empi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…These findings support previous studies that suggest men are more isolated across the lifecourse than females (Umberson et al, 2022;Read et al, 2020), and could indicate that men living alone have reduced positive health behaviours (Berkman et al, 2000). Study members born in the 1970 BCS cohort were also more likely to belong to classes experiencing multiple forms of isolation, supporting previous research that showed an increase in some forms of social isolation over time in the UK (Mansfield et al, 2024).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…These findings support previous studies that suggest men are more isolated across the lifecourse than females (Umberson et al, 2022;Read et al, 2020), and could indicate that men living alone have reduced positive health behaviours (Berkman et al, 2000). Study members born in the 1970 BCS cohort were also more likely to belong to classes experiencing multiple forms of isolation, supporting previous research that showed an increase in some forms of social isolation over time in the UK (Mansfield et al, 2024).…”
Section: Discussionsupporting
confidence: 88%
“…In the current study, a lack of frequent contact with friends and relatives outside of the household was defined as less than monthly contact and few study members reported isolation on this domain. In contrast, a lack of community engagement, based on not being a member of a community group or organisation, less than monthly religious activity and a lack of volunteering was highly prevalent in these cohorts (Mansfield et al, 2024). It could be that there is a wellbeing benefit for the minority who regularly engage with their community, but given that not doing so has become normalised, a significant increase in psychological distress is not observed.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations